On fractional integral operators of three variables and integral transforms - Khan, Mumtaz Ahmad (Pontificia Universidad Católica del Perú, 2011)
The present paper is a continuation to authors paper [11]where three variable analogues of certain fractional integraloperators of M. Saigo were investigated. This paper dealswith the effect of operating three variable analogues of Mellinand Laplace transforms on these three variable analogues offractional integral operators of the earlier paper.
Keywords: Cuerpos valorados henselianos; Cuerpo cuerpo real cerrado; Sistema de monomios; https://purl.org/pe-repo/ocde/ford#1.01.00